Evidence On The Incremental Information-Content Of Additional Firm Disclosures Made Concurrently With Earnings - Hoskin, Re; Hughes, Js; Ricks, We (Journal of Accounting Research, 1986)
Information content, Disclosures, Dividends, Earnings components